Gamification in Remote Teaching of SE Courses: Experience Report - Lelli, Valéria; Andrade, Rossana M. C.; Freitas, Lavinia M.; Silva, Rubens A. S.; Filho, Francisco Gutenberg S.; Gomes, Renata Faria; Severo, Jan Sousa de Oliveira (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Distance education is understood as well-planed online learning mediated by computer technologies. Online learning involves more planning and design decisions and thus it is more rigorous than Emergency Remote Teaching (ERT). Given the COVID-19 pandemic several undergraduate and graduate classroom courses had to adapt their traditional classes to ERT. In this context, we have adapted our methodology based on face-to-face classes to incorporate the gamification as a strategy to deal with ERT. The goal of this paper is to present the remote methodology based on the gamification that we have applied on two Computer Science courses. To use the gamification, we have selected a free online gamification, called Classcraft, that enable us to use asynchronous tools. In our methodology, we first organized the course' contents into modules and then, for each module, we defined the activities to work the module's topics; the interactions between the professor and students; and the evaluation criteria. The results showed that the gamification as ERT strategy is effective to engage the students during the pandemic. However, they had difficulties to understand the purpose of using asynchronous tools such as forum.